REAL TEACHING : PROFESIONALISME MAHASISWA PPL PROGRAM STUDI PENDIDIKAN SOSIOLOGI STKIP BIMA DI KOTA BIMA - Nurnazmi (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2018)
Professional teachers have the characteristics as based on Law No. 14 of 2005, among others: having pedagogical competence, personality competence, professional competence and social competence. The STKIP Bima Sociology Education Study Program which has teacher background holds real teaching or Field Experience Practices (PPL) with 107 PPL students with a total of 843 students from various study programs located in Bima City and Bima Regency. The research method used is descriptive qualitative. The research informants were students in social studies majors in grades X and XI, science class X and class XI. Data collection techniques used are observation, interviews and documentation. The data analysis technique according to Mile and Huberman has three stages (data reduction, data display and data verification). Testing the validity of the data using data triangulation. The research analyst uses the structural functional theory of Robert King Merton. The results of this study relate to the performance of PPL teachers and the competence of professional teachers. The performance of PPL teachers experienced a dominant increase in student assessment in the second month of implementation. Professional teacher competency consists of pedagogic competencies, personality competencies, professional competencies and social competencies. Pedagogical competencies are more emphasized on methods, media, and learning strategies. Personality competency, the teacher is still not firm in controlling students who make noise. Professional competence, the teacher still lacks mastery of the material so that it has an impact on the delivery of piecemeal material, rigid and forgetfulness. Social competence, teachers always remind and direct students how important the future is.